Gender difference in effects of proprioceptive neuromuscular facilitation stretching on flexibility and stiffness of hamstring muscle - Yu, Suiqing; Lin, Lihua; Liang, Hongying; Lin, Ming; Deng, Weixin; Zhan, Xinshu; Fu, Xihua; Liu, Chunlong (Frontiers in Physiology, 2022)
Abstract Objective: This study investigated the acute effects of PNF stretching on hamstring flexibility and muscle stiffness of lower limbs between genders. Methods: 15 male and 15 female university students without any injury histories on lower limbs in the past 3 months were included in this study were selected. All subjects were measured by MyotonPRO before and after stretching to determine the muscle stiffness of the biceps femoris muscle (BF), semitendinosus muscle (ST) of the hamstring and the medial gastrocnemius muscles (MG), lateral gastrocnemius muscles (LG), and the soleus(SOL)of the triceps surae muscles. Additionally, their flexibility was measured for the sit-and-reach test(the SR test) and passive hip range of motion (ROM). Differences based on time (pre-stretching vs post-stretching) and sex (females vs males) were assessed using 2 X 2 repeated measures AVONA. Results: There was a significant decrease in the stiffness of the hamstring and triceps surae muscles after stretching(BF, MG, LG, and SOL: P<0.001; ST: P=0.003). The muscle stiffness of the hamstring and triceps surae muscles is larger in males than in females at all time points(P<0.001). There was a significant increase in hip flexion angle and the SR test in males and females after PNF stretching(P<0.001); However, there was no difference in the change in the muscle stiffness and the flexibility between genders (P>0.05). Conclusion: PNF stretching helped improve hamstring flexibility and decrease muscle stiffness. Stretching the hamstrings can also contribute to a decrease in the stiffness of the triceps surae muscles. The muscle stiffness of males before and after stretching is always greater than that of females. However, there was no difference in the change of improvement in stretching between genders.